The Effectiveness of Group Counseling (Support Group Technique) in Improving Self-Esteem between Adolescent with Bullying Behavior - Feri Agustriyani; Ardinata Ardinata; Sugiarto Sugiarto; Rika Damayanti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Bullying remains a major challenge in Indonesian schools, including Pringsewu, with negative impacts on adolescents’ mental health, academic performance, and social well-being. If not addressed, it may disrupt emotional development and cause long-term trauma. Low self-esteem is often linked to vulnerability, making adolescents prone to becoming either victims or perpetrators. This study aims to explore how enhancing self-esteem can serve as an effective strategy for bullying prevention. A quantitative quasi-experimental design was applied using a pre-test and post-test with a control group. The sample included 100 students from Senior High School State One of Ambarawa, Pringsewu Regency, divided into 50 participants in the intervention group and 50 in the control group. Data were analyzed using paired samples T-test. Results showed a significant improvement in self-esteem within the intervention group (p = .000 ≤ 0.05), demonstrating the effectiveness of support group counseling. The control group also showed significance (p = .017) but with weaker impact. These findings highlight that group counseling can effectively strengthen self-esteem, thereby reducing vulnerability to bullying behaviors. In conclusion, support group techniques and similar counseling approaches can play an important role in creating supportive school environments, enhancing resilience, and mitigating bullying among adolescents.